Fire Performance Enhancement of Natural-Fiber-Reinforced Polymer Composites - Wahyu Purwo Raharjo; Dody Ariawan; Kuncoro Diharjo; Wijang Wisnu Raharjo; Bambang Kusharjanta (New Approaches in Engineering Research Vol. 15, 2021)
Thermal stability, fire resistance and fire retardation of natural fiber reinforced polymer composites is reviewed in this book chapter. Despite offering higher specific mechanical properties, one of the major restrictions in application of polymer-natural fiber composites in engineering sector is their susceptibility to heat and flame. Hence, thermal decomposition and burning mechanism of natural fibers, polymer matrix and polymer-natural fibers composites are important knowledge to select the material required and develop the composite products. Furthermore, the thermal stability and fire resistance of the composites can be improved by the presence of suitable flame retardants (FRs). Several conventional types of FRs are discussed including their mechanism of flame retardation, advantages and limitations. Some potential FRs, which are based on biomass, are introduced to reduce the negative environmental effect of conventional types. They are considered as eco-friendly and renewable due to their bio-based nature. Hence, these types are named as green FRs. Their influence on fire performance, advantages and drawbacks also discussed.